Biomedical engineering yesterday, today, and tomorrow. - Ghista, D.N.
Today, biomedical engineering (BME) in tertiary medical care involves functions such as: medical monitoring (e.g., PET visualization of brain receptors to identify neuronal dysfunction); medical diagnosis (e.g., computer-aided echocardiographic texture analysis to detect myocardial infarcts); radiation therapy (for cancer treatment); organ-support (e.g., peritoneal dialysis); therapeutic function (e.g., encapsulation of insulin-producing pancreatic islet cells for treatment of diabetes). However, is biomedical engineering a relatively new field? Not really, although one may have opened up new vistas of it. In the past, science was not so compartmentalized into material science, engineering science, and life science. Hermann von Helmholtz (1821-1894), who determined the velocity of pulse-propagation in nerves, was professor of both physiology and physics. On the German 10 DM note is depicted (along with the familiar bell-shaped probability distribution curve) the portrait of Carl Friedrich Gauss (1777-1855). Ranking as one of the greatest mathematicians of all times, he also made important contributions to astronomy, geodesy, and electromagnetism. It is this spirit, to explore and bring to bear physical and engineering sciences as well as psychology to medical and clinical sciences, that constitutes the future of biomedical engineering. A modern and intrinsic concept is that of internal biomedical engineering or organ systems engineering, entailing analyses of organ functional mechanisms and processes. Biomedical engineering development of both macro and micro body processes can eventually lead to more intrinsic and reliable diagnostic methodologies. However, the author first visits a hitherto relatively unexplored phenomenon associated with vital (life) engineering, namely the role of consciousness in health and disease. This approach has in fact been a long-standing tradition in Eastern systems of medicine.
Keywords: Carl Friedrich Gauss; Eastern systems of medicine; Hermann von Helmholtz; PET visualization; Bell-shaped probability distribution curve; Brain receptors; Computer-aided echocardiographic texture analysis; Consciousness; Diabetes; Engineering science; Insulin-producing pancreatic islet cells; Life science; Macro body processes; Material science; Medical diagnosis; Medical monitoring; Micro body processes; Nerve pulse-propagation velocity; Organ-support.; Peritoneal dialysis; Radiation therapy; Tertiary medical care; Therapeutic function